(K+5)/2=(k-4)/5

Simple and best practice solution for (K+5)/2=(k-4)/5 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (K+5)/2=(k-4)/5 equation:



(+5)/2=(K-4)/5
We move all terms to the left:
(+5)/2-((K-4)/5)=0
We add all the numbers together, and all the variables
-((K-4)/5)+5/2=0
We calculate fractions
(-((K-4)*2)/()+()/()=0
We calculate terms in parentheses: +(-((K-4)*2)/()+()/(), so:
-((K-4)*2)/()+()/(
We add all the numbers together, and all the variables
-((K-4)*2)/()+1
We multiply all the terms by the denominator
-((K-4)*2)+1*()
We calculate terms in parentheses: -((K-4)*2), so:
(K-4)*2
We multiply parentheses
2K-8
Back to the equation:
-(2K-8)
We add all the numbers together, and all the variables
-(2K-8)
We get rid of parentheses
-2K+8
Back to the equation:
+(-2K+8)
We get rid of parentheses
-2K+8=0
We move all terms containing K to the left, all other terms to the right
-2K=-8
K=-8/-2
K=+4

See similar equations:

| 17x+20=19x-8 | | K+37-2(k-4)4=1 | | 4-x=-13-8+3x+x | | 49(2)+2x=146 | | 5x+6x-9x=20 | | -34x=-20 | | c=16-(-8) | | 4d-6=d-21 | | -4.5x27=45 | | 5+6x+9x=20 | | 0.99d=10+88d | | 4-(2+3x)=2x+9=11+6x | | 49x^2-4x=15 | | 4(s+7)=85 | | -2x+2=-30 | | 146=(2)49+2x | | 4x+3x=9x+4 | | -32=-15=a | | 2x-11+2x-6+x=180 | | -2x+2=30 | | 9.1x+900=82.81+30x | | -30h=45 | | 13+8(5x-9=21 | | -15-3=t | | 2+1.25f=10-2.85 | | 3y+2y=9y+4 | | 8/n+2=12 | | 2x-3(4x)=-10 | | 6.64x+66.4=132.8 | | 3k+10=21+3k | | x(2)-10=18x | | 5x-2+4=16 |

Equations solver categories